Body extractivism: subjective conditions and the expansion of productive frontiers in neoliberal capitalism - Seré, Cecilia (Las Torres de Lucca. International Journal of Political Philosophy, 2025)
This paper thinks the body as a significant category for understanding the present time. The starting point lies in the study of the relationship individuals establish with their bodies, considering that the social relations of production that structure capitalism presuppose a relationship of each individual with themselves. This social organization based on the production of value organizes the relationship with the body in terms of private property, a legal and subjective structure necessary for wage labor. From there, it is shown that the modulations occurring in the neoliberal capitalist scenario expand the sources for the extraction of value, developing extractivist mechanisms on the body. The traditional valorization of labor power directly linked to available physiological knowledge expands its boundaries towards unexplored spaces of subjective tissue. Neoliberal life organized around the imperative of self-production capitalizes on capacities, skills, and subjective competences that privatize personal management and precarize existence. If fatigue was the manifestation of bodily limits in industrial capitalism, depression, anxiety, and stress are expressions of the exhaustion produced by this organization of life based on bodily fracking.